Optimizing plant density and weed control techniques in yield enhancement of mungbean - Joarder, Sabbir Mahmud; Ali, Md Hazrat; Hossain, HMM Tariq; Chowdhury, Imtiaz Faruk; Rahman, Md Mahfuzar (Journal of the Asiatic Society of Bangladesh, Science, 2016)
Field experiment was carried out at the Agronomy farm, Sher-e-Bangla Agricultural University, Dhaka, Bangladesh to investigate the effect of plant density and weed control techniques on yield enhancement of mungbean. The experiment consisted of two factors viz. plant densities and weed control. Plant densities were 30 cm×continuous (D1), 30 cm×5 cm (D2), 30 cm×10 cm (D3) and 30 cm×15 cm (D4) arranged in the main plot. Weed control techniques were no weeding (W0), two hand weeding at 15 and 30 DAS (W1), Topstar 80 WP @ 75 g ha-1 as pre-emergence at 3 DAS (W2) and Whip Super 9 EC @ 750 ml ha-1 at 15 and 30 DAS as post-emergence herbicide (W3) arranged in the sub plot in a split plot design. Results showed that both plant density and weed control techniques significantly influenced most of the parameters studied. It was observed that application of pre and post emergence herbicide controlled weeds effectively compared to other weed control techniques whereas weed population and weed biomass were less in 30 cmx10 cm plant density. Considering yields, combination of 30 cm×10 cm plant density with application of Topstar 80 WP (D3W2) attributed to highest seed yield (1.47 t ha-1), stover yield (1.94 t ha-1) and biological yield (3.41 t ha-1) of mungbean. J. Asiat. Soc. Bangladesh, Sci. 42(1): 107-114, June 2016